Long-term stability of large insert genomic DNA episomal shuttle vectors in human cells. - Wade-Martins, R; Frampton, J; James, MR (1999)
We have constructed an episomal shuttle vector which can transfer large (>100 kb) human genomic DNA inserts back and forth between bacteria and human cells and which can be tracked in rapidly dividing human cells using a live cell assay. The vector (p5170) is based on the F factor-derived bacterial artificial chromosome cloning vector used in Escherichia coli, with the addition of the family of repeats element from the Epstein-Barr virus (EBV) latent origin of replication. This element provides nuclear retention in cells expressing the EBV protein EBNA-1. We have subcloned a series of genomic DNA inserts into p5170 and transfected the constructs into an EBNA-1(+) human cell line. Episomal mitotic stability was quantitatively analysed using flow cytometry. The episomes were also tracked by time course photography of expanding colonies. A 117 kb episome was retained at approximately 2 copies/cell and could be shuttled unrearranged from the human cells into bacterial cells after 15 months of continuous cell growth. Furthermore, the episome could still be rescued from human cells cultured in the absence of selection for 198 days. Such a trackable E.coli /human cell line shuttle vector system capable of carrying >100 kb of genomic DNA in human cells could prove a valuable tool in gene expression studies.